Increased intermediate M1‐M2 macrophage polarization and improved cognition in mild cognitive impairment patients on ω‐3 supplementation. Issue 1 (27th September 2016) - Famenini, Sam; Rigali, Elizabeth A.; Olivera‐Perez, Henry M.; Dang, Johnny; Chang, Michael To; Halder, Ramesh; Rao, Rammohan V.; Pellegrini, Matteo; Porter, Verna; Bredesen, Dale; Fiala, Milan
Abstract : Monocyte/macrophages of patients with mild cognitive impairment (MCI) and Alzheimer disease (AD) are defective in phagocytosis and degradation amyloid β1–42 (Aβ1–42 ), but are improved by ω‐3 fatty acids (ω‐3s). The hypothesis of this study was that active Aβ1–42 phagocytosis by macrophages prevents brain amyloidosis and thus maintains cognition. We studied the effects of self‐supplementation with a drink with v‐3s, antioxidants, and resveratrol on Mini‐Mental State Examination (MMSE) scores, macrophage M1M2 phenotype [the ratio of inflammatory cluster of differentiation (CD)54+CD80 and proresolution markers CD163+CD206], and Aβ1–42 phagocytosis in patients initially diagnosed as having MCI or subjective cognitive impairment (SCI). At baseline, themedian MMSE score in patients in both the apolipoprotein E (ApoE) ε3/ε3 and ApoE ε3/ε4 groups was 26.0 and macrophage Aβ1–42 phagocytos is was defective. The MMS Erate of change increased in the ApoE ε3/ε3 group a median 2.2 points per year ( P =0.015 compared to 0) but did not change in the ApoE ε3/ε4 group(P = 0.014 between groups). In the ApoE ε3/ε3 group, all patients remained cognitively stable or improved; in the ApoE ε3/ε4 group, 1 recovered from dementia, but 3 lapsed into dementia. The macrophage phenotype polarized in patients bearing ApoE ε3/ε3 to an intermediate (green zone) M1‐M2 type at the rate of 0.226 U/yr, whereas in patients bearing ApoE ε3/ε4, polarization was negative ( P = 0.08 between groups). The baseline M1M2 type in the extreme M1 (red zone) or M2 (white zone)was unfavorable for cognitive outcome. Aβ1–42 phagocytosis increased in both ApoE groups ( P =0.03 in each groups). In vitro, the lipidic mediator resolvin D1 (RvD1) downr egulated the M1 type in patients with ApoE ε3/ε3 but in some patients with ε3/ε4, paradoxically up‐regulated the M1 type. Antioxidant/v‐3/resveratrolsupplementationwas associatedwith favorable immuneandcognitive responses in ApoE ε3/ε4 and individual patients bearing ApoE ε3/ε4, and brings into personalized clinical practice the immune benefits expected from ω‐3 mediators called resolvins. The validity of this study is limited by its small size and uncontrolled design.—Famenini, S., Rigali, E. A., Olivera‐Perez, H. M., Dang, J., Chang, M T., Halder, R., Rao, R. V., Pellegrini, M., Porter, V., Bredesen, D., Fiala, M. Increased intermediate M1‐M2 macrophage polarization and improved cognition in mild cognitive impairment patients on ω‐3 supplementation. FASEB J. 31, 148–160 (2017) www.fasebj.org